Improving field production of ergot alkaloids by application of gametocide on rye host plants - Hanosová, Helena; Koprna, Radoslav; Valík, Josef; Knoppová, Lucie; Frébort, Ivo; Dzurová, Lenka; Galuszka, Petr (New biotechnology, 2015)
Ergot alkaloids are widely used in the pharmaceutical industry in drug preparations for treating migraines and Parkinson's disease, inducing uterine contraction, and other purposes. Phytopathogenic fungi of the genus Claviceps (e.g. C. purpurea) comprise a major biological source of ergot alkaloids. Worldwide industrial production of these alkaloids derives almost equally from two biotechnological procedures: submerged culture of the fungus in fermenters and field parasitic production in dormant fungal organs known as sclerotia (also termed ergot). Ergot yields from field cultivation are greatly affected by weather and also can be much reduced by pollen contamination from imperfectly male-sterile rye, as only unfertilized ovaries can be infected by C. purpurea spores. Two substances with gametocidal effect - maleic hydrazide and 2-chloroethylphosphonic acid - were tested during three consecutive seasons in small field experiments for the ability to induce or amplify the male sterility of rye as well as the impacts on germination of C. purpurea spores and general vitality of rye host plants. Maleic hydrazide was proven to be a highly effective gametocide on both a fertile rye variety and a variety with imperfectly induced cytoplasmic male sterility. It showed negligible effect on germination of C. purpurea spores. Both accurate dosaging of the active gametocidal compound and timing of the application just 2-3 weeks before onset of anthesis proved crucial to achieving high ergot yield with minimum grain impurities.
Keywords: Up-Regulation; námelové alkaloidy; regulátory růstu rostlin; Ergot Alkaloids; Organophosphorus Compounds; zárodečné buňky rostlin; Secale; upregulace; Germ Cells, Plant; hydrazid kyseliny maleinové; žito; Maleic Hydrazide; vztah mezi dávkou a účinkem léčiva; neplodnost rostlin; Dose-Response Relationship, Drug; Plant Infertility; Plant Growth Regulators; organofosforové sloučeniny